Halsted Radicalmastectomy: Technique Modification - Lucas, Hiram Silveira (2023)
A modification to the classic HALSTED's method for radical mastectomy is described with the conservation of the major pectoral muscle. The A. is performing succesfully for the last three years such modification consisting in the transversal sectioning of the costochondral branch of fibers of the major pectoral muscle for large exposition and ressection of the axiliar-subclavian vesels and nerves. The monoblock surgical specimen contains the minor pectoral muscle as well as both anterior and posterior major pectoral aponeurosis. The presented technique differs fundamentally from the original HALSTED's method for the best esthetic resuits with the "fulfilment" of the subclavicular fossa due to the two leveis suture of the conserved major pectoral muscle.